Giao thoa văn hóa trong giao tiếp ngôn ngữ và trong dạy-học tiếng Nga = Cross-culture in language communication and in Russian teaching and learning /Dương Quốc Cường. - Dương, Quốc Cường.
Language is a special product of history and society, closely connected with the national culture throughout its development. Each language community has its own logic of thinking and experience of language communication with generalization and specification at different levels of language and language practice. The 1960s, 1970s marked the occurrence of the term “culture” in linguistics, especially the “cross-cultural” concept introduced by a number of famous linguists. This approach to language makes the field of linguistics research more diverse than ever. This article is to discuss the cross-culture in expressing language and suggest impacts of cross-culture in discourse in Russian teaching and learning.